Dust Removal Mechanism of the Vibrating String Filter with Charged Water Mist - Zuyun Chen; Ziyi Zhou; Jicheng Peng (International Journal of Rotating Machinery)
The traditional dust removal technology is difficult to meet the strict requirements of environmental protection, so it is of practical significance and research value to study how to purify fine dust in workshop. Fine dust can be suspended in the atmosphere, while reducing the air quality. Excessive inhalation of dust may result in disease. So it should be paid close attention to dust control. The water mist charging process has experienced three stages: induction charge, corona charge transition, and corona charge. When the discharge distance is 80 mm, the charge-mass ratio of droplet and the current of water mist are most affected by corona voltage. The significant impact analysis of orthogonal experiment is studied. The result of the orthogonal experiment is analyzed by the variance method. It is noted that the inlet wind speed has the highest influence, and the discharge distance has a least influence on the dust removal efficiency. The discharge distance is 80 mm, and the voltage working band is suitable for the normal voltage regulation of the electrostatic precipitator. The condensation efficiency of charged droplets on dust is beneficial to reduce the negative effect of excessive wind speed on wet vibrating string grid and to improve the effective handling volume of dust collector. The charge-mass ratio of water mist is improved effectively, and the dust removal efficiency is increased in the vibrating string filter with charged water mist. Theoretical analysis and experimental studies showed that the vibrating string filter with charged water mist is as a new composite efficient dust removal technology that can effectively deal with the purification of fine dust particles in the gas stream, especially in respiratory dust removal.